Gut microbiome and serum metabolome alterations in osteosarcoma patients - Li, Chao; Chen, Yu; Yao, Weitao; Zhang, Peng; Wang, Xin; Qu, Guoxin; Ren, Zhigang; Wang, Jiaqiang (Frontiers in Microbiology, 2025)
BackgroundGut microbiota has been shown to initiate tumorigenesis and cancer metastasis in multiple cancer types. However, the functional alterations of gut microbiota and their association with metabolism in osteosarcoma patients remain largely unexplored. This study aimed to characterize the gut microbiota and serum metabolite profiles in osteosarcoma patients, evaluate the diagnostic potential of gut microbiota and serum metabolites for osteosarcoma, and explore their correlations.MethodsWe collected 128 fecal and 181 serum samples from osteosarcoma patients, paired with matched healthy controls. 16S rRNA sequencing and untargeted metabolomics were applied to analyze gut microbiota and serum metabolism with significantly altered abundance in patients with osteosarcoma. Models based on gut microbiome or serum metabolites were established and evaluated in an independent validation cohort.ResultsThe gut microbial diversity decreased in osteosarcoma patients compared to healthy individuals. Principal component analysis identified 33 microbial species that exhibited significant changes in osteosarcoma patients. Of note, the relative abundance of Alloprevotella and Prevotella increased in these patients. This distinct alteration in gut microbiota was accompanied by functional changes in pathways related to glycan degradation, pentose and glucuronate interconversions, the citrate cycle, and fructose and mannose metabolism during osteosarcoma progression. Furthermore, metabolomic analyses revealed a distinct distribution of serum metabolites in osteosarcoma patients compared to healthy controls. These metabolites were correlated with cancer’s carbon metabolism, glucagon signaling, and the citrate cycle pathways. Combined with the enrichment analysis results, gut microbiota and serum metabolites were associated with carbohydrate-related metabolism in osteosarcoma patients. Importantly, classifiers utilizing 3 optimal microbial markers (6 serum metabolites) demonstrated strong diagnostic efficiency in distinguishing osteosarcoma patients from healthy controls across various cohorts.ConclusionThis study thoroughly analyzed gut microbiota and serum metabolites in osteosarcoma patients, exploring their correlations and facilitating the establishment of a diagnostic model.